The Effect of Audio Visual Education Range of Motion on Family Motivation in increasing muscle strength through ROM training in post-stroke patients at home: Audio Visual Education Range of Motion on Family Motivation - Ixora Ixora; Dewi Wulandari; Rahayu Niningasih; Edi Yuswantoro (Poltekkes Kemenkes Malang, 2024)
: Family support during the rehabilitation phase is very much needed in order to improve the quality of life of post-stroke patients. Poor delivery of information and coordination between health teams causes family knowledge about disease management to be incomplete. Counseling and education is one of the pillars of managing stroke patients. The nurse's obligation is to provide education and ensure the transition of care to the family as a care agent for the patient at home. Identification of family members for educational purposes requires paying attention to educational background and productive age level. This research aims to examine the influence of health education about ROM on family motivation in carrying out ROM in stroke infarction patients in the family. The research design used is Quasi Experimental Design using a one group model pre test - post test design. The population in this study were all families of stroke patients in the Durenan Community Health Center Working Area.The research results showed that before health education regarding ROM was carried out, there were 25 respondents (83.3%) who had sufficient motivation to carry out ROM in stroke infarction patients. After health education about ROM, there were 20 respondents (66.7%) who had the motivation to carry out ROM in stroke infarction patients in the good category. The results of quantitative data analysis using the Wilcoxon signed ranks test statistic with the help of the SPSS computer program can be interpreted as statistical test results with a significance of 0.05 resulting in a value of P Value = 0.000 which is smaller than the value of a = 0.05 (0.000 < 0.05) so that H0 rejected and H1 accepted, which means there is an influence of health education about ROM on family motivation in carrying out ROM for infarction stroke patients in the Durenan Community Health Center Working Area.In accordance with the research instrument carried out by the researchers, it was found that after health education about ROM was carried out using audio-visual media, it was found that there was an increase in family motivation in carrying out ROM for family members who had suffered a stroke. This needs to be given attention and efforts must be made so that health workers can continue to provide health education about ROM to patient families so that families can be motivated and play an active role in helping to carry out ROM for family members who suffer from stroke.